Optimizing title and Meta tags based on distribution of keywords; Lexical and semantic approaches - Farahmand, Mohammad; Md Sultan, Abu Bakar; Azmi Murad, Masrah Azrifah; Sidi, Fatimah (Science Publications, 2011)
Problem statement: To increase traffic on websites, Search Engine Optimization (SEO) has provided many costly and time-consuming options. One problem is the inadequate distribution of keywords especially those keywords that users use the title tag and Meta tags. Approach: This study described work on an initial model for handling some of the SEO factors to increase the distribution of keywords. Our purposed model provide users with the words and their values based on the key weights with initiated formula to provide a new title, keywords, or description in order to increase the relativity between content and HTML Meta tags and title tag. Results: The proposed model had been showed evidence of gaining the greater utilization of the distribution of keywords and prevents recognition of search engine spam. Conclusion: The result shows the significant enhancement of the proposed model on Title Weight by 51.69% of original Title Weight defined by user.